(untitled) (Oshada, 2025)
The increasing prevalence of type 2 diabetes in urban areas highlights the urgency of multidimensional interventions that go beyond conventional clinical approaches. Rapid urbanization, obesogenic environments, and unequal access to healthy food reinforce the social determinants of health, which systematically trigger metabolic risks. This study used qualitative methods through a review of current literature to identify patterns, structural determinants, and the effectiveness of community empowerment as a prevention strategy. The analysis shows that individual-based programs often fail due to a lack of environmental support, the dominance of ultra-processed foods, and economic barriers. Community empowerment has been shown to improve health literacy, strengthen positive social norms, and trigger active participation in advocacy for healthier environmental policies. The findings emphasize the need for public policy reforms to regulate the food industry, expand physical activity spaces, and direct budget allocations toward prevention efforts. Cross-sectoral integration, including urban planning, education, and active transportation, fosters the sustainability of interventions. Community capacity building has the potential to create stronger collective health resilience than top-down approaches. Therefore, the synergy between community empowerment and structural policies is considered a comprehensive strategy to control the epidemiological trends of diabetes in urban areas. This study highlights the need to reposition the role of communities as key actors in the urban health ecosystem.